Behaviour of masonry load bearing walls retrofitted with GFRP composites - SinghPrakash, S. Suriya; Alagusundaramoorthy, P. (Journal of Structural Engineering, 2025)
Masonry buildings are the major building stocks around the world that fail in earthquakes due to their low tensile and shear resistance. To improve the strength and enhance the seismic performance of masonry structures, a new technique of retrofitting using GFRP composites is explored. The main objective of this investigation is to develop a finite element model for the analysis of masonry structures and to study the effectiveness of retrofitting these masonry structures using GFRP composites. The material response for masonry was modeled using the smeared crack concrete material model available in the finite element software ABAQUS. Inplane loads were applied monotonically both in vertical and horizontal directions and the resistance of masonry load bearing shear and flexure specimens were studied. Different strengthening schemes such as X-bracing, full surface bonding and two end straps using GFRP composites were studied using the developed finite element model. Parametric studies were also carried out on the effect of vertical compression, increase in the number of layers, change in the fiber orientations on the lateral load carrying capacity of load bearing brick masonry walls. Based on this study it is concluded that the ultimate strength and deformational capacity can be increased by retrofitting the masonry load bearing walls with full surface bonding of GFRP composite fabric.